Menthae Herba Attenuates Neuroinflammation by Regulating CREB/Nrf2/HO-1 Pathway in BV2 Microglial Cells - Yeo Jin Park; Hye Jin Yang; Wei Li; You-Chang Oh; Younghoon Go (Antioxidants, 2022)
Chronic inflammation and oxidative stress cause microglia to be abnormally activated in the brain, resulting in neurodegenerative diseases such as Alzheimer’s disease (AD). Menthae Herba (MH) has been widely used as a medicinal plant with antimicrobial, anti-inflammatory, and antioxidant properties. In this study, we sought to evaluate the effects of MH on the inflammatory response and possible molecular mechanisms in microglia stimulated with lipopolysaccharide (LPS). Transcriptional and translational expression levels of the proinflammatory factors were measured using ELISA, RT-qPCR, and Western blot analysis. MH extract inhibited the production of proinflammatory enzymes and mediators nitric oxide (NO), NO synthase, cyclooxygenase-2, tumor necrosis factor-α, and interleukin-6 in LPS-stimulated cells. Our molecular mechanism study showed that MH inhibited the production of reactive oxygen species (ROS) and the phosphorylation of mitogen-activated protein kinase and nuclear factor (NF)-κB. In contrast, MH activated HO-1 and its transcriptional factors, cAMP response element-binding protein (CREB), and the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathways. Thus, MH reduces ROS and NF-κB-mediated inflammatory signaling and induces CREB/Nrf2/HO-1-related antioxidant signaling in microglia. Together, these results may provide specific prospects for the therapeutic use of MH in the context of neuroinflammatory diseases, including AD.